The Effect of Lower-Body Strength Training Using Ankle Weights on the Straight-Kick Ability of Athletes from the IKSPI Kera Sakti Timika - Wahyuni, Baiq Sri; Sutirta, Habibi; Letisia, Maria (Champions: Education Journal of Sport, Health, and Recreation, 2026)
In general, Pencak Silat techniques include punches, kicks, grabs, throws, takedowns, locks, blocks, backhand strikes, scratches, thrusts, strikes, slashes, and jabs. (Gunawan. A, 2007). A physical component that plays a significant role in every sport, including Pencak Silat, is lower-body explosive power. Ankle weight training is an exercise designed to enhance the strength and performance of the lower-body muscles, performed by applying weight to the lower legs (Girsang & Hasibuan, 2012). The research was conducted at the IKSPI Kera Sakti Pencak Silat Academy in Timika, Papua. This was a pre-experimental study. The design was a one-group pretest-posttest design. The results of this study indicate that there is a significant effect of lower-body power training using the ankle-weight method on the straight-kick ability of athletes from the IKSPI Kera Sakti Timika, as evidenced by a pretest average score of 10.13, which increased in the posttest, with the average score for straight-kick ability reaching 15.20. The t-test results also show that the calculated t-value of 8.264 > the critical t-value of 1.7613 (df 14), with a significance level of p = 0.000 < 0.05. Based on the research results, it is concluded that “There is a significant effect of lower-body muscle power training using the Ankle Weight Method on straight-kick ability among athletes at the IKSPI Kera Sakti Timika.